Quality Improvement Of Long Distance Learning Program In Magister Of Informatics Engineering Telkom University Using Qfd Method - Prima Annisa Karunia; Yati Rohayati; Rio Aurachman (eProceedings of Engineering, 2016)
Long Distance Learning (LDL) is one of the government's program to increase the number of university students in Indonesia. Telkom University (Tel-U) is one of the universities that provide LDL Program for postgraduate students. One of the majors in Telkom Graduate School which is the object of this research is Master of Informatics Engineering (MIF). LDL MIF Tel-U has yet to reach the target number of students each year due to the lack of quality of services provided. Therefore, LDL MIF Tel-U needs to improve the quality in order to achieve the targets set. This research aims to provide recommendations to improve the quality of LDL MIF Tel-U services based on nine true customer needs using Quality Function Deployment (QFD) method. QFD is one of the quality improvement method that focus on Voice of Customer (VoC). QFD calculation that is used in this research is QFD two iterations, which are the House of Quality (HOQ) to determine the technical requirement and Part Deployment Matrix to determine the critical part. Recommendation formulation drawn up by the data processing and concept selection using decision matrices, analysis of brainstorming with LDL MIF Tel-U, as well as benchmark to the competitor that aims to develop the service quality of LDL MIF Tel-U. The recommendations given are, increasing the number of servers, adding both speed internet access, increased bandwidth, updating software versions of lectures, replacing video conference software, adding the number of communication with lecturers, controlling the development of the curriculum each year, training related to the world of work, and change the file sharing application. Keywords: LDL, QFD, MIF, Tel-U